Autohesion of polymers. (5th August 2016) - Awaja, Firas
Abstract: Autohesion (direct-bonding or self-bonding) is the formation of bonds between two surfaces of an identical polymer at elevated temperature (usually just above T g ). It is an emerging technique that has the potential to cleanly and precisely join/bond polymers without the need for adhesives. Autohesion is particularly useful for applications that require hermetic and precise polymer bonding, such as in microfluidics, MEMS, and in the encapsulation of active medical implants. This article discusses the latest debate on the main mechanisms proposed to explain autohesion of polymers such as diffusion, crystalline growth, thermodynamic and chemical bonding. Surface activation techniques that are used to facilitate autohesion such as plasma treatment, chemicals, UV and ozone treatments are explored. In addition, topics such as molecular characteristics of polymers that influence autohesion, limits to bonding strength and hermetic bonding are critically discussed. Methods for evaluating autohesion strength of polymers are also described. Comparisons between prediction models from different research groups with experimental values for authohesive bonding strength are shown. Finally, conclusions and suggestions for further research are presented. Graphical abstract: Highlights: This article discusses the latest debate on the main mechanisms proposed to explain autohesion of polymers such as diffusion, crystalline growth, thermodynamic and chemical bonding. Surface activation techniques that are used to facilitate autohesion such as plasma treatment, chemicals, UV and ozone treatments are explored. In addition, topics such as molecular characteristics of polymers that influence autohesion, limits to bonding strength and hermetic bonding are critically discussed. Methods for evaluating autohesion strength of polymers are also described. Comparisons between prediction models from different research groups with experimental values for authohesive bonding strength are shown.